Calibrating Strain Measurements: A Comparative Study of DAS, Strainmeter, and Seismic Data - Chih‐Chieh Chien; Peter Gerstoft; William Hatfield; Leo Hollberg; Bradley P. Lipovsky; John‐Morgan Manos; Robert J. Mellors; Dale P. Winebrenner; Mark A. Zumberge (Earth and Space Science)
Abstract Significant interest has developed in using optical fibers for seismology through Distributed Acoustic Sensing (DAS). However, converting DAS strain measurements to actual ground motions can result in errors and uncertainties due to imperfect coupling of the fiber to the earth and instrument response functions. To address this, we conducted a comparative analysis of strain data recorded by DAS, Optical Fiber Strainmeters (OFSs), and estimates derived from seismic data. This study used dark fibers in a commercial cable connecting two islands in Puget Sound, Washington, USA. The cable extends from a telecommunication substation on Whidbey Island, through an underground conduit, and across Saratoga Passage to Camano Island. The strain along the cable was recorded using OFS Michelson interferometers and a DAS interrogator, with a broadband seismometer positioned at one end. Comparing a teleseismic earthquake recording showed that summed DAS channels agreed well with OFS recordings. The amplitude discrepancies between the measurements and the seismometer's estimated strain indicated poor coupling between the cable and the earth. We also evaluated DAS amplitude response using a piezoelectric cylinder (PZT) to generate ground truth strain. The findings revealed a notable amplitude decrease in DAS recordings at lower frequencies, highlighting the need for amplitude calibration. Moreover, some underwater signals in the study area were strongly correlated with the velocity of the tidal current. These signals can be localized through coherence calculations between the DAS and OFS recordings.